Enhanced oxidation properties of ZrB2–SiC composite with short carbon fibers at 1600 °C. Issue 11 (1st June 2021) - He, Linkai; Sun, Youhong; Meng, Qingnan; Liu, Baochang; Wu, Jinhao; Zhang, Xuliang
Abstract: This study investigated the effect of short carbon fiber (Cf ) on the oxidation behavior of ZrB2 –SiC composites with fiber volume fractions in the range of 0–20%. Precisely, highly dense composite compacts were manufactured by hot-press process at 2000 °C and 30 MPa for 60min. The addition of Cf increased the relative density of sintered composite The oxidation treatment at 1600 °C in air tube furnace for 0.5 h revealed that oxidation rate of ZrB2 –SiC-Cf composites decreased from 292.4 μm/h to 77.6 μm/h (almost 73.5% decline), when the content of Cf changed from 0 to 20%. Moreover, Cf played important roles in blocking and deflecting oxygen diffusion during the oxidation process, which provided a local reduction environment of oxidation products.